Examining the effect of HPV vaccination in order to prevent cervical cancer – a systematic review - Alinezhad, Nasim (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
The present study investigated the effect of human papillomavirus (HPV) vaccination in preventing cervical cancer. In the current study, 63 articles published in 2010–2024 were reviewed with keywords including “cervical cancer”, “HPV”, and “uterine cancer” in PubMed, Scopus, Science Direct, Elsevier and Wiley databases. The risk ratio of cervical cancer screening was 1.15 times (HR = 1.15; 95% CI: 0.18–2.21) higher among HPV-vaccinated women than unvaccinated women. Women with two doses of HPV vaccine were more likely to initiate screening (HR = 1.66; 95% CI: 0.43– 2.89; I 2 = 0). Receiving at least one dose of HPV vaccination was associated with a higher rate of cervical cancer screening, which reduces the risk of cervical cancer by increasing the number of doses to two and three doses, and with more timely screening, cervical cancer can be detected.